The Institutional Dualism and Its Impact on Economic Development The Case of Dualism in Batam - Lany Pionier S; Jun Matsunami; Bakti Setiawan (Politeknik Negeri Batam, 2019)
Batam as a region with a strategic position, located on the international trade route, was developed to become one of the engines of economic growth in Indonesia. However, in its development, Batam faced governance problems that had an impact on the decline in its economic performance. Not only at the local level, but its influence reaches the national level. This study explains the causal relationship of Dual Governance, focusing on aspects of formation, relations between institutions and their impact on development. Using the framework of Holzinger, Kern and Kromrey (2016), this study captures the issue of institutional dualism that has occurred for years and is considered to be the cause of the decline in development in Batam. The study was conducted using qualitative research methods with a case study approach and collecting data from interviews and document analysis.There are several concluding points in this study regarding institutional dualism and its impact on economic development based on Batam’s case. They are the implementation of decentralization, the significance of the pre-existing institution, the similarity between two institution in respect of interpreting and implementing policies and the relationship between intergovernmental relations and economic development. These three factors affect the degree of intergovernmental relations which is directly proportional to economic development. The more intergovernmental relations are, the higher economic development is.